High-Order Angle and Polarization Resolved Reflection of Artificial Opal Photonic Crystal - Le, Dac Tuyen; Vu, Dinh Lam (Communications in Physics, 2018)
We present angle resolved reflection measurements showing the polarization dependence of photonic band gap in artificial opal photonic crystals. The SiO2 opals were prepared using thermal-assisted cell method. The observation of well-defined diffraction pattern indicates the samples with high quality. The reflection measurements were analyzed in the high energy region up to a/l = 1.6. It is shown that the diffraction peaks depend on s- and p-polarized light illumination. The polarization anisotropy effect due to symmetric properties of opal structure. The experiment results agree fairly well with calculated photonic band structure and are also discussed with predictions based on group theory. Angular reflection has implications in polarized light scattering in plasmonic structures and metamaterials and is also useful in applications like nano scale polarization splitters and lasers